Repositioning Nutrition as Central to Development : a Strategy for Large Scale Action. - Bank, World (Directions in development (Washington, D.C.), 2005)
Persistent malnutrition is contributing not only to widespread failure to meet the first MDG-to halve poverty and hunger-but to meet other goals in maternal and child health, HIV/AIDS, education, and gender equity. The choice is now between continuing to fail, or to finally make nutrition central to development. Underweight prevalence among children is the key indicator for measuring progress on non-income poverty and malnutrition remains the world's most serious health problem and the single biggest contributor to child mortality. Nearly a third of children in the developing world are either.